Myocarditis Secondary to Mesalamine-Induced Cardiotoxicity in a Patient with Ulcerative Colitis - Kelechukwu U. Okoro; Matthew D. Roby; Adegbenga A. Bankole (Case Reports in Medicine)
Development of cardiac manifestations in patients diagnosed with inflammatory bowel disease undergoing treatment with mesalamine is a rare. When this occurs, it can be difficult to tease out the primary etiology, as both IBD and mesalamine can cause cardiac manifestations independently of each other. The exact mechanism of mesalamine-induced cardiotoxicity is yet to be determined although several mechanisms have been described. We present the case of a gentleman with nonexertional chest pain in the setting of ulcerative colitis exacerbation believed to have occurred secondary to mesalamine.